Leveraging productivity through leader capacity and leader engagement in the hospitality industry - Pramanik, Purwanti Dyah; Rahmanita, Myrza; Nurbaeti, Nurbaeti; Ingkadijaya, Rahmat (Technium Social Sciences Journal, 2025)
Hospitality businesses face significant challenges in increasing productivity. One factor critical to improving productivity concerns the capacity and engagement of the leader. The study aimed to analyse the impact of leader capacity on productivity mediated by leader engagement in the hotel sector. To determine how leader capacity influences productivity through leader engagement. A quantitative approach was employed. The population consisted of 71 general managers in a four-star hotel in Jakarta. A sample of 56 respondents was used. The sample was chosen by purposive sampling. The results indicated that leader capacity significantly influences productivity directly and through leader engagement. Analysing the leader’s capacity to increase productivity is noteworthy for the hotel sector. Inadequate hotel productivity can be improved by strengthening a leader’s capacity to reach engagement, which impacts leader productivity. This study outlined leader capacity and engagement as critical to retaining leader productivity.